Comparative Analysis of Steel and Timber Truss Structural Strength in Shophouse Buildings Using the Structure Analysis Program Method - Ninik Paryati (Newinera Publisher, 2026)
Wood and steel trusses are two types of materials commonly used in building roof structures, each with its own advantages and disadvantages in terms of strength, durability, cost, aesthetics, and other aspects. This study examines steel and wood trusses from the aspect of strength by designing both types of trusses and then determining the quality of wood and steel materials for analysis using a structural analysis program. The truss design has a span of 18 m with a roof slope of 30°, and the trusses are spaced 2 m apart. The total area of the shop-house building is 12 m × 18 m = 216 m², with a height of 4 m. The truss material uses steel with a grade of BJ 37, while the wood is grade A. The structure of the shop-house uses concrete with a strength of 25 MPa. The dead load consists of a uniform load of 50 kg/m² for the trusses and 150 kg/m² for the shop-house. The live load for the roof (liveroof) is 50 kg/m², while the live load for the shop-house floor is a uniform load of 100 kg/m². The load combination used in the analysis is 1.2D + 1.6L + 0.5Lr. The analysis results show that the bending moment, shear force, and axial force of the steel truss are greater than those of the wood truss because the self-weight of the steel truss is higher than that of the wood truss. The deflection of both steel and wood trusses remains within the allowable limit of 0.3, indicating that the deflections are safe. Based on the structural design check, both steel and wood trusses are safe to use.